2007
DOI: 10.2174/138920007780655450
|View full text |Cite
|
Sign up to set email alerts
|

Role of P-Glycoprotein in the Intestinal Absorption of Tanshinone IIA, a Major Active Ingredient in the Root of Salvia miltiorrhiza Bunge

Abstract: The extracts from the roots of Salvia miltiorrhiza Bunge (Danshen) are widely and traditionally used in the treatment of angina pectoris, acute myocardial infarct, hyperlipidemia and stroke in China and other Asian countries. In this study, we have investigated the role of P-glycoprotein (P-gp) in the intestinal absorption of tanshinone IIA (TSA), a major active constituent of Danshen, using several in vitro and in vivo models. The oral bioavailability of TSA was about 2.9-3.4% in rats, with non-linear pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…17 The complexity of this aforementioned interplay within the larva may contribute to the loss of activity upon 18 h of pre-exposure prior to treatment with PTZ. Other less-active or inactive tanshinones may also play a role in either improving the compounds' penetration into the fish's system by modulating the drug-efflux pumps present in cells 18,19 in a similar fashion to those in bacteria 20 and cancer cells 21 or by modifying the solubilities of the active compounds. 17 Because the lipophilic fraction of danshen has not been fully explored for its potential anticonvulsant effects in earlier literature, the identified active tanshinones bear further analysis, along the lines of structure−activity relationships.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…17 The complexity of this aforementioned interplay within the larva may contribute to the loss of activity upon 18 h of pre-exposure prior to treatment with PTZ. Other less-active or inactive tanshinones may also play a role in either improving the compounds' penetration into the fish's system by modulating the drug-efflux pumps present in cells 18,19 in a similar fashion to those in bacteria 20 and cancer cells 21 or by modifying the solubilities of the active compounds. 17 Because the lipophilic fraction of danshen has not been fully explored for its potential anticonvulsant effects in earlier literature, the identified active tanshinones bear further analysis, along the lines of structure−activity relationships.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The poor absorption of tanshinones may have been due to their low aqueous solubility and limited membrane permeability [20]. Yu et al [21] reported that cryptotanshinone is a substrate for P-gp, and that P-gp mediated efflux of cryptotanshinone into the gut lumen. Thus low oral bioavailability was also attributed to the first-pass effect.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, we [1,[10][11][12][13][14][15][16][17][18][19] and others [20][21][22][23][24] have demonstrated that TSN has potential protective effects against atherosclerosis, cardiac hypertrophy, cardiac fibrosis, diabetes, neurodegenerative diseases, and various kinds of cancers. However, the poor water-solubility, poor intestinal absorption, and low oral bioavailability (about 2.9 --3.4% in rats) [25] have hampered the clinical application of TSN. To overcome these problems, various approaches have been employed, such as the preparation of water-soluble derivative of TSN-sodium tanshinone II-A sulfonate (STS) [4], the preparation of TSN in discoidal and spherical HDL [26], and the development of new drug delivery systems for TSN such as solid dispersion pellets, nanoparticles, and microemulsions [26].…”
Section: Tanshinone Ii-amentioning
confidence: 99%